2009
DOI: 10.1783/147118909788707986
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards the male contraceptive pill in men and women in casual and stable sexual relationships

Abstract: Background and methodology Men's and women's attitudes towards the male contraceptive pill and their trust in the effective use of the male pill were investigated, as well as the associated variables of reported health behaviours, perceived self-efficacy and type of sexual relationship, using a questionnaire survey. ResultsAlthough both sexes had a favourable attitude towards the male pill, females had a more positive attitude than men. Conversely, women had less trust that men would use the male pill effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 30 publications
(32 reference statements)
2
29
1
1
Order By: Relevance
“…Thus, Brooks [12] examined the views of 115 males in Bristol in the south west, and found that the contraceptive pill was well accepted, especially amongst males in established relationships. These results were similar to those of Eberhardt et al [14]. In their age-and gender-matched sample of 110 males and 110 females in the north east of England, women on the whole had a more positive attitude than men; however, males in a stable sexual relationship were more willing to accept the male pill than those in unstable or casual sexual relationships.…”
Section: Hypothetical Acceptabilitysupporting
confidence: 88%
See 4 more Smart Citations
“…Thus, Brooks [12] examined the views of 115 males in Bristol in the south west, and found that the contraceptive pill was well accepted, especially amongst males in established relationships. These results were similar to those of Eberhardt et al [14]. In their age-and gender-matched sample of 110 males and 110 females in the north east of England, women on the whole had a more positive attitude than men; however, males in a stable sexual relationship were more willing to accept the male pill than those in unstable or casual sexual relationships.…”
Section: Hypothetical Acceptabilitysupporting
confidence: 88%
“…Would women trust their partners to use a male pill efficiently, and would men trust themselves? Glasier et al [24] researched the attitudes of 1,894 women in Scotland (450), China (900) and South Africa (544), and found that only 36 women (2%) believed that they would not trust their partners, which threatens the idea that new forms of male contraception would not be successful for reasons of trust.This is contradictory to the findings of Eberhardt et al [14], who found, in their aforementioned sample of men and women in the north east of England, that women had less trust that men would use the male pill effectively than men themselves, despite there also being a lack of confidence in its effective use amongst these men, especially in casual relationships. Their results also revealed that being female and having trust in men's effective use of the male pill reliably predicted a positive attitude, while being male, being involved in casual sexual relationships or in no relationship, and having low trust in its effective use each reliably predicted a negative attitude.…”
Section: Trustcontrasting
confidence: 81%
See 3 more Smart Citations